2014
DOI: 10.1017/s0956536114000133
|View full text |Cite
|
Sign up to set email alerts
|

Maya Coastal Production, Exchange, Life Style, and Population Mobility: A View From the Port of Xcambo, Yucatan, Mexico

Abstract: Anchored in archaeological, bioarchaeological, and chemical research conducted at the coastal enclave of Xcambo, this paper examines Classic period Maya coastal saline economic production and exchange, along with the lifestyle, ethnicity, and mobility of the traders. Nestled in the coastal marshlands of the northern Yucatan, Mexico, Xcambo functioned as a salt production center and port during its occupation, maintaining long-reaching ties with other parts of the Maya world and Veracruz. Considered together, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…Table 1 shows strontium isotopic and concentration results. Salt samples collected at coastal production sites (Celestun, Xtampu) on the north and northwest coast of the Yucatan Peninsula have 87 Sr/ 86 Sr values that are similar to those expected for modern seawater (Hodell et al, 1991(Hodell et al, , 2007 and that are found at nearby archaeological sites (Price et al, 2008;Sierra Sosa et al, 2014). The Pacific coast sample (Sipacate) has a 87 Sr/ 86 Sr value that is strikingly different than those associated with the volcanic bedrock geology in the region.…”
Section: Resultsmentioning
confidence: 58%
“…Table 1 shows strontium isotopic and concentration results. Salt samples collected at coastal production sites (Celestun, Xtampu) on the north and northwest coast of the Yucatan Peninsula have 87 Sr/ 86 Sr values that are similar to those expected for modern seawater (Hodell et al, 1991(Hodell et al, , 2007 and that are found at nearby archaeological sites (Price et al, 2008;Sierra Sosa et al, 2014). The Pacific coast sample (Sipacate) has a 87 Sr/ 86 Sr value that is strikingly different than those associated with the volcanic bedrock geology in the region.…”
Section: Resultsmentioning
confidence: 58%
“…We must remember, however, that while the whole population commonly ingested fruits, honey and tamales, other ingredients (like cacao) were oftentimes limited to the society's wealthier class (Cucina et al, 2011). In this perspective, the elevated socio-economic status of the population of Xcambó (Sierra Sosa et al, 2014), in particular during the Late Classic, permitted them to access also this kind of foodstuff. The picture that emerges based on the kind of foodstuff and food recipes is that the bucco-lingual CEJ lesions might have been triggered also by the ingestion of sugary sticky fruits and not just by starchy ones.…”
Section: Discussionmentioning
confidence: 99%
“…The skeletal sample was excavated between 1996 and 2000 by one of the authors (TSS, -National Institute of Anthropology and History, Yucatan Center) (Sierra Sosa, 1999;Sierra Sosa et al, 2014). The skeletal collec-tion is currently housed at the Bioarchaeology and Histomorphology Laboratory, School of Anthropological Sciences, Autonomous University of Yucatan (UADY).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, generally low amounts of obsidian across the northern lowlands (not counting Chunchucmil) during this period would suggest anemic long-distance trade. Yet the flourishing port of Xcambo (Sierra Sosa 1999;Sierra Sosa et al 2014) and the evidence of interaction with Central Mexico at Chunchucmil and other northern lowland sites (varela Torrecilla and Braswell 2003;Smyth 2006; see chapter 12, this volume) suggest the possibility of a network of interaction as opposed to the clearly bounded interaction spheres typical of solar central place systems. Nevertheless, the distance from Chunchucmil to the next large marketplace would have been much further than the distance between marketplaces in an interlocking market system like that of the Basin of Mexico in the Postclassic period (Blanton 1996).…”
Section: Discussionmentioning
confidence: 99%